Parental mediation of the internet in Singapore. - Chan, Aloysius Yan Ming. (2011)
The study examined how parental mediation of adolescents’ Internet use can be affected by key antecedents such as family communication patterns (FCPs), parents’ perceived online literacy, parents’ perception of the Internet and socio-demographic factors such as parental income, parental education level, ethnicity and the child’s gender. A survey consisting of items measuring these variables was administered to a sample of 205 parents. An analysis of the results indicated that patterns of parental mediation patterns online were far more unpredictable than we had expected and predicted based on our review of literature. In particular, the directions of correlations of parental mediation with FCP and demographic predictors sometimes ran in contrary to what has been documented in previous studies, such as how parental income levels was found to be linked to restrictive mediation methods. It should be noted, however, that previous studies were largely based on television mediation, and as such, perhaps there is a need to develop new models of mediation which would apply better to the unique medium of the Internet. Such differences also suggest the need for a country and culture-specific investigation in order to help policy-makers better devise appropriate Internet-use regulations, as most prior research has been conducted in the West.